Fluorescence measurement of metal uptake by pathogenic bacteria - Kumar, Ashish (Kansas State University, 2021)
The increasing antibiotic resistance of Gram-negative bacteria, e.g., Enterococcus, Staphylococcus, Klebsiella, Acinetobacter, Pseudomonas, and Enterobacter (ESKAPE) pathogens, calls for increased efforts to search for novel chemical agents that target microbial pathways. Bacterial iron acquisition pathways are potentially relevant in the search for new antibiotics. Iron is vital to bacteria because it plays a central role in energy production, DNA synthesis, intermediate metabolism, nitrogen fixation, and oxygen detoxification. At the time of infection or colonization in the host environment, bacteria must acquire iron to proliferate. To do so, they secrete small molecular weight organic compounds, siderophores, that bind iron with high affinity. They also express outer membrane (OM) transporters that recognize and internalize the ferric siderophore complex. Especially, Gram-negative bacteria acquire iron using TonB dependent ferric siderophore transport system. For example, the OM protein FepA actively transports ferric enterobactin (FeEnt) in the periplasm, and the inner membrane (IM) protein TonB provides energy for this ferric siderophore uptake reaction. We originally devised a fluorescence spectroscopic approach that observes real-time ferric-siderophore in E. coli, e.g., FeEnt uptake through the OM receptor, FepA. This method monitors the binding of the FeEnt to the outer loops of fluorescently labeled FepA. Binding quenches fluorescence, but fluorescence recovers as the bacteria transport and deplete the ferric siderophore from the solution. Hence, inhibitors that block the active transport of the siderophore prevent fluorescence recovery. We adapted this approach to functionally characterize multiple Klebsiella pneumoniae ferric enterobactin transporters and also applied the methodology to study other ferric siderophore transport reactions. Despite the sensitivity and accuracy of this species-specific approach, experimental manipulations of ESKAPE pathogens are always concerning points due to potential hazardousness. Hence, we modified the assay in a manner where it allowed the observation of ferric siderophore transport by any of the ESKAPE pathogens, including clinical isolates, without genetically engineering them. A TonB-deficient bacterium, with fluorescently labeled OM receptor, acts as a sensor strain that binds ferric siderophore but cannot transport it. When cohabiting in an environment with other bacterial pathogen, the sensor strain monitored ferric siderophore uptake and thereby TonB action in that bacterial pathogen. We created “Universal” assays of TonB dependent Ferric siderophore transport by any bacterial pathogen with such sensor strains. Using these species-specific and universal assays, it is plausible to look for those compounds that can inhibit TonB action and prevent ferric siderophore transport. These chemicals that block TonB action may inhibit iron acquisition in humans and animals and thereby thwart pathogenesis. Such chemicals may act as novel therapeutics against bacterial infectious diseases. We used these fluorescent sensors to detect, discriminate, and quantify ferric siderophores in purified form or complex mixtures of metabolites and other biochemicals. We created fluorescent sensors from different bacterial species that recognized different metal complexes: native (FeEnt), glucosylated (FeGEnt), degraded (FeEnt*) ferric enterobactin; the hydroxamates: ferrichrome (Fc), ferric acinetobactin (FeAcn), ferric aerobactin (FeAbn), and ferrioxamine B (FxB); the porphyrins: hemin (Hn) and vitamin B12. In spectroscopic assays, these constructs sensitively detected and quantified the different metal chelates in solution. We showed biochemical specificity, affinity, and membrane transport using these sensors. The sensors are helpful in detecting, discriminating siderophores, and providing diagnostic information about bacterial presence in clinical and food samples. In the later part, using these fluorescence decoy sensors, we also looked at the mechanistic part of FeEnt transport through FepA. We concluded that rearrangements must occur in the globular N-domain of FepA during FeEnt transport. We suggested that N-domain does not exit the transmembrane channel as a rigid body in the periplasm; instead, it remains within the transmembrane pore as FeEnt enters the periplasm.
Keywords: Fluorescent sensors; Bacterial iron transport; Decoy sensors; Cys substitutions; TonB dependent transport; Siderophores; ESKAPE pathogen